Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1080/0042098022000011362
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Improved Retail Access on Diet in a 'Food Desert': A Preliminary Report

Abstract: If poor food retail access in deprived areas of British cities is linked, as suggested in many of the policy debates of the late 1990s, via compromised diets/undernutrition to poor health and widening health inequalities, what is the impact of a sudden and significant improvement in food retail access likely to be on the food consumption patterns of residents? In this paper, we describe and provide preliminary results from the first-ever UK study of a major retail provision on diet in a 'food desert'—a 'before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
199
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(207 citation statements)
references
References 12 publications
2
199
0
1
Order By: Relevance
“…The context of this study is however even different to that previous work in that the intervention was specifically intended to result in storeswitching behaviour amongst consumers in the deprived area, and indeed amongst those who could most benefit from a more 'healthy' diet. The only similar research appears to be the Seacroft study introduced above , but it did not relate storeswitching behaviour to previous work (they did suggest a rate of 45% of shoppers switching to the new Tesco store but more detailed and specific retention/switching rates are not presented) (Wrigley, 2002b). This explicit welfare approach and the limited previous work on store-switching behaviour invites a number of research questions:…”
Section: C) Research Objectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…The context of this study is however even different to that previous work in that the intervention was specifically intended to result in storeswitching behaviour amongst consumers in the deprived area, and indeed amongst those who could most benefit from a more 'healthy' diet. The only similar research appears to be the Seacroft study introduced above , but it did not relate storeswitching behaviour to previous work (they did suggest a rate of 45% of shoppers switching to the new Tesco store but more detailed and specific retention/switching rates are not presented) (Wrigley, 2002b). This explicit welfare approach and the limited previous work on store-switching behaviour invites a number of research questions:…”
Section: C) Research Objectivesmentioning
confidence: 99%
“…This involved an uncontrolled before-and-after 'intervention' (the intervention being a new Tesco superstore) study of changes in food consumption patterns in a highly deprived area. Wrigley et al (2002bWrigley et al ( , 2003 concluded that there were significant improvements post-intervention in terms of food retail access, accompanied by improved diet amongst some groups of…”
Section: A) Retail-led Regeneration and Food Desertsmentioning
confidence: 99%
See 2 more Smart Citations
“…In such localities, consumers are highly dependent on convenience stores as they often provide the only remaining access to grocery stores, with the consequence that consumers in these areas tend to pay higher prices and have a more restricted diet (Whelan et al 2002). At the other extreme, a handful of major studies have explored the effect of provision interventions from the opening of major multiple-owned superstores in food deserts in Leeds (Wrigley et al 2002a;Wrigley et al 2003;Wrigley et al 2002b) and Glasgow (Cummins et al 2008), attempting to assess the effects on diet. These findings provide contrary evidence that such large-scale initiatives have a positive effect on the dietary patterns of local households.…”
Section: Enhancing Consumer Choice and Accessmentioning
confidence: 99%